2020
DOI: 10.3389/fimmu.2020.00407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4 and CXCR7 Is Protective in Acute Peritoneal Inflammation

Abstract: Our previous studies revealed a pivotal role of the chemokine stromal cell-derived factor (SDF)-1 and its receptors CXCR4 and CXCR7 on migratory behavior of polymorphonuclear granulocytes (PMNs) in pulmonary inflammation. Thereby, the SDF-1-CXCR4/CXCR7-axis was linked with adenosine signaling. However, the role of the SDF-1 receptors CXCR4 and CXCR7 in acute inflammatory peritonitis and peritonitis-related sepsis still remained unknown. The presented study provides new insight on the mechanism of a selective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 76 publications
1
17
0
Order By: Relevance
“…In addition, unlike CCR5, which interacts with several types of ligands, CXCR4 has an exclusive ligand known as SDF-1. As reported, the interaction between CXCR4 and SDF-1 mainly regulates the generation, transport, homing and retention of CXCR4-positive blood cells in hematopoietic organs and the accumulation of CXCR4-positive immune cells in inflammatory sites (34)(35)(36)(37)(38). Previous studies have shown that SDF-1 correlated with HIV infection, cardiovascular disease and the mobilization of hematopoietic stem and progenitor cells (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 79%
“…In addition, unlike CCR5, which interacts with several types of ligands, CXCR4 has an exclusive ligand known as SDF-1. As reported, the interaction between CXCR4 and SDF-1 mainly regulates the generation, transport, homing and retention of CXCR4-positive blood cells in hematopoietic organs and the accumulation of CXCR4-positive immune cells in inflammatory sites (34)(35)(36)(37)(38). Previous studies have shown that SDF-1 correlated with HIV infection, cardiovascular disease and the mobilization of hematopoietic stem and progenitor cells (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 79%
“…Because the protective effects of the anesthetic were greatest 1 h after zymosan installation, we chose this time point for all subsequent experiments, including fecal-induced peritonitis experiments as described previously. 17…”
Section: Peritonitis Models and Applicationmentioning
confidence: 99%
“…With a Vectastain ABC kit, neutrophil accumulation in the intestine, lung, and liver tissue was visualized by immunohistochemistry (Vector Laboratories, Germany) as previously described. 17 Tissue slides were processed with a Leitz DM IRB microscope (Leica, Germany) and analyzed with AxioVision, version 4.8.2 (Carl Zeiss, Germany).…”
Section: Immunohistochemical Neutrophil Detectionmentioning
confidence: 99%
“…Although PMs did not express detectable cell surface levels of CXCR4, they did respond to stimulations of CXCL12, and its expression increased during acute inflammatory peritonitis ( 48 , 49 ). The increased expression of CXCR4 in macrophages under inflammation stimuli explained the increased amount of CD68+ macrophages after modeling and increased proportions of PMs at the 10 and 18 th weeks when the intestinal inflammation response aggravated alongside CRC development.…”
Section: Discussionmentioning
confidence: 94%